Contracts, Tools, Verification - Leino, Rustan (ASWEC 2010, Auckland, New Zealand, 2010)
We want to develop software… with the right features that is easy to use that is hard to misuse accidentally maliciously can be developed effectively on schedule free of defects can be maintained to add features to adapt to new environments to preserve/transfer knowledge between developers